Analisis Manajemen Risiko Terhadap UMKM “Kedai Teman Makan” - Rahmawati, Repa; Amalia, Annisa Yunda; Fauziyah, Lidya (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This analysis aims to identify the risks faced by the "Teman Makan" shop. Through in-depth analysis of the business environment, operational processes and other internal factors, this analysis reveals various potential risks that could threaten business continuity. It is hoped that the results of this research can become a basis for the "Teman Makan" shop in developing effective risk mitigation strategies. Risk management is an important aspect in the sustainability of a food shop business. This research analyzes various risk strategies that can be implemented by "Teman Makan" to develop an early warning system, service suppliers and improve the quality of customer service. The goal at the end of this analysis is to increase the resilience of the "Teman Makan" shop to various uncertainties that may occur. The “Teman Makan” shop faces various challenges in a dynamic business environment. This analysis can disrupt the store's operations and profitability. Next, develop an integrated risk management framework, starting from risk identification, risk analysis, to strategy development. By implementing a risk management approach, the "Teman Makan" shop is expected to increase its advantages and achieve success in the long term.